Personality and temperamental dimensions of effective management - Strzałecki, Andrzej; Kusal, Agnieszka (Studia Psychologica: Theoria et praxis, 2002)
The senior author’s model of The Style of Creative Behavior together with Strelau’s Regulative Theory of Temperament, and Rotter’s Locus of Control Theory were used to explain effective management under systems transformation in Poland. The multiple R of the instruments chosen to measure respective theories were as follows: Strzalecki’s Creative Behavior Questionnaire (R=0,964), Strelau’s Formal Characteristic of Behavior – Temperament Inventory (R=0,796), Gliszczynska’s Internal-External Locus of Control Questionnaire (R=0,750). When all instruments were taken into consideration the best R came from three factors of The Creative Behavior Questionnaire: Strength of Ego, Self-realization, and Internal Source of Valuation (multiple R=0,964) The results seem to corroborate a threshold hypothesis of the relation between temperament and managerial effectiveness. To a certain point, the temperamental dimensions, especially Reactivity, play an important role in coping with stress induced in managerial activity. Then  personality factors related to creative behavior become more important. The article ends with a discussion about the concept of an effective personality syndrome in creative management and innovative entrepreneurship.